Circulating neutrophil subsets in advanced lung cancer patients exhibit unique immune signature and relate to prognosis. Issue 3 (19th January 2020) - Shaul, Merav E.; Eyal, Ophir; Guglietta, Silvia; Aloni, Pazzit; Zlotnik, Asaf; Forkosh, Ester; Levy, Liran; Weber, Lukas M.; Levin, Yonathan; Pomerantz, Alon; Nechushtan, Hovav; Eruslanov, Evgeniy; et al.
Abstract: The accumulation of circulating low‐density neutrophils (LDN) has been described in cancer patients and associated with tumor‐supportive properties, as opposed to the high‐density neutrophils (HDN). Here we aimed to evaluate the clinical significance of circulating LDN in lung cancer patients, and further assessed its diagnostic vs prognostic value. Using mass cytometry (CyTOF), we identified major subpopulations within the circulating LDN/HDN subsets and determined phenotypic modulations of these subsets along tumor progression. LDN were highly enriched in the low‐density (LD) fraction of advanced lung cancer patients (median 7.0%; range 0.2%‐80%, n = 64), but not in early stage patients (0.7%; 0.05%‐6%; n = 35), healthy individuals (0.8%; 0%‐3.5%; n = 15), or stable chronic obstructive pulmonary disease (COPD) patients (1.2%; 0.3%‐7.4%, n = 13). Elevated LDN (>10%) remarkably related with poorer prognosis in late stage patients. We identified three main neutrophil subsets which proportions are markedly modified in cancer patients, with CD66b + /CD10 low /CXCR4 + /PDL1 inter subset almost exclusively found in advanced lung cancer patients. We found substantial variability in subsets between patients, and demonstrated that HDN and LDN retain a degree of inherent spontaneous plasticity. Deep phenotypic characterization of cancer‐related circulating neutrophils and their modulation along tumor progression is an important advancement in understanding the role of myeloid cells in lung cancer.